Changes in bone mineral density over time by body mass index in the health ABC study. Issue 6 (June 2016) - Lloyd, J.; Alley, D.; Hochberg, M.; Waldstein, S.; Harris, T.; Kritchevsky, S.; Schwartz, A.; Strotmeyer, E.; Womack, C.; Orwig, D.
Abstract Summary Obesity appears protective against osteoporosis in cross-sectional studies. However, results from this longitudinal study found that obesity was associated with bone loss over time. Findings underscore the importance of looking at the longitudinal relationship, particularly given the increasing prevalence and duration of obesity among older adults. Introduction Cross-sectional studies have found a positive association between body mass index (BMI) and bone mineral density (BMD), but little is known about the longitudinal relationship in US older adults. Methods We examined average annual rate of change in BMD by baseline BMI in the Health, Aging, and Body Composition Study. Repeated measurement of BMD was performed with dual-energy X-ray absorptiometry (DXA) at baseline and years 3, 5, 6, 8, and 10. Multivariate generalized estimating equations were used to predict mean BMD (femoral neck, total hip, and whole body) by baseline BMI (excluding underweight), adjusting for covariates. Results In the sample (n  = 2570), 43 % were overweight and 24 % were obese with a mean baseline femoral neck BMD of 0.743 g/cm2, hip BMD of 0.888 g/cm2, and whole-body BMD of 1.09 g/cm2 . Change in total hip or whole-body BMD over time did not vary by BMI groups. However, obese older adults lost 0.003 g/cm2 of femoral neck BMD per year more compared with normal weight older adults (p  < 0.001). Femoral neck BMD change over time did not differ between the overweight and normal weight BMI groups (p  = 0.74). In year 10, adjusted femoral neck BMD ranged from 0.696 g/cm2 among obese, 0.709 g/cm2 among normal weight, and 0.719 g/cm2 among overweight older adults. Conclusions Findings underscore the importance of looking at the longitudinal relationship between body composition and bone mineral density among older adults, indicating that high body mass may not be protective for bone loss over time.